Planificarea și evaluarea politicilor publice în domeniul asistenței sociale - Daniel Arpinte (Sociologie Românească, 2019)
The main objective of the study is to analyse how the public policies in the area of social assistance are planned and evaluated in Romania. The first part of the study presents how the social assistance policies have been integrated into the social inclusion strategies, in a in try to identify the main priorities, as well as the way in which the strategic measures have been implemented in five key areas: broadening and development of public social assistance system, professionalisation of public social assistance services, connections between strategic strands in social assistance, social assistance financing, and monitoring and evaluation of social assistance system. The analysis is done in a broader context of planning an evaluation of public policies in Romania, a relatively new practice adopted by the public administration. The study underlines the state of the social assistance system from the perspective of each above mentioned area and tries to identify the main results of the implementation of the strategies. The available data shows that despite that, starting with 2002, the strategies from social inclusion area have included specific measures for social assistance, the results are modest, particularly in the area of community services, which has negative consequences on the capacity of the entire system to provide support for those in need. The public local social assistance services have a low rate of professionalisation, being weakly integrated into the county services system, which might generate an increase cost of the services, rather aiming to diminish the effects of the social problems than to prevent them. The social assistance remains marginalised, the previous achievements being rather a result of some incidental or particular investments, without a clearly defined vision about the role of public social assistance system.